2016
DOI: 10.1021/acs.jpclett.6b02420
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-Induced Structural Evolution and Band Gap Shifts of Organometal Halide Perovskite-Based Methylammonium Lead Chloride

Abstract: Organometal halide perovskites are promising materials for optoelectronic devices. Further development of these devices requires a deep understanding of their fundamental structure-property relationships. The effect of pressure on the structural evolution and band gap shifts of methylammonium lead chloride (MAPbCl) was investigated systematically. Synchrotron X-ray diffraction and Raman experiments provided structural information on the shrinkage, tilting distortion, and amorphization of the primitive cubic un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

13
113
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(129 citation statements)
references
References 44 publications
13
113
0
Order By: Relevance
“…[12] The hydrophobic molecules in the organic layers effectively improve the moisture resistance compared to the 3D perovskite, which solves the main obstacle of 3D OIHPs. [21][22][23][24][25] For example, Wang et al studied the structural transition and photoresponse of CH 3 NH 3 PbBr 3 (MAPbBr 3 ) under pressure. [15,16] The alternating layers of 2D lead-halide perovskites induce an exceptionally large exciton binding energy [15,17] and a wide band gap in contrast to 3D lead-halide perovskites, which limits its optical performance.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[12] The hydrophobic molecules in the organic layers effectively improve the moisture resistance compared to the 3D perovskite, which solves the main obstacle of 3D OIHPs. [21][22][23][24][25] For example, Wang et al studied the structural transition and photoresponse of CH 3 NH 3 PbBr 3 (MAPbBr 3 ) under pressure. [15,16] The alternating layers of 2D lead-halide perovskites induce an exceptionally large exciton binding energy [15,17] and a wide band gap in contrast to 3D lead-halide perovskites, which limits its optical performance.…”
mentioning
confidence: 99%
“…[23] Lv et al found that the structural stability and photoresponsiveness of CH 3 NH 3 SnI 3 enhanced after pressureinduced amorphization and recrystallization. [23] Lv et al found that the structural stability and photoresponsiveness of CH 3 NH 3 SnI 3 enhanced after pressureinduced amorphization and recrystallization.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…25 First, the pressure-induced variation of the properties of hybrid perovskites for solar-energy cells (see also MRS Bulletin, May 2014 26 and August 2015 27 ) are illustrated and discussed in parallel with the chemically induced changes that occur by substituting different halides or organic ligands. [28][29][30] The authors illustrate how the bandgap and carrier lifetime-both critical for solar application-could be influenced by substitution or by substrate selection, thus suggesting new (potentially pressure-influenced) directions of approach to longstanding issues. The second class of materials are manganites, which show exceptional magnetic and electronic functional diversity.…”
Section: Chemistry At High Pressurementioning
confidence: 99%
“…[28] Therefore, we performed high-pressureR amane xperiments on the Cs 3 Sb 2 I 9 crystals to effectively track the evolution of the vibrational modes of [Sb 2 I 9 ] 3À octahedra. [28] Therefore, we performed high-pressureR amane xperiments on the Cs 3 Sb 2 I 9 crystals to effectively track the evolution of the vibrational modes of [Sb 2 I 9 ] 3À octahedra.…”
mentioning
confidence: 99%